Preliminary findings of malnutrition risk factors among older adults in a care home - Abdul Aziz, Siti Al-Baidakh; Mohd Yusof, Barakatun Nisak; Omar, Noraida (Community Health Society Malaysia, 2019)
Background: Older adults are at risk of nutrient deficiencies. They face many barriers to have an adequate intake that leads to malnutrition Among Malaysian institutionalized elderly aged 60 years and above, the prevalence of malnutrition was 17.4% and it was associated with eating half of the food served in the institution. Materials and Methods: This cross-sectional study aimed to determine the association between adequacy of nutrition provision and plate wastage with risk of malnutrition among elderly aged ≥ 60 years in Rumah Seri Kenangan, Cheras (RSK) (N=46). The study used Mini Nutritional Assessment (MNA) to assess malnutrition risk, weighing method for adequacy and plate waste study. Mean of energy and protein (served, consumed and wasted) were compared with the Malaysian Recommended Nutrient Intake (RNI). Results: Majority of the subjects were male (65%; n=30) and 35% were females (n=16). Mean age of the subjects was 71.35±7.21 years. Majority of the subjects were classified as well-nourished (50%) and 13% as malnourished. Total energy served in one-lunch time was inadequate (82.67±12.93% of RNI) but total protein served was adequate (108.59±19.63 % of RNI). Total energy and protein consumption were inadequate with the mean percentage of RNI for energy and protein was 47.09±26.39% and 73.50±32.07% respectively. Surprisingly, energy and protein served, consumed and wasted were not associated with risk of malnutrition. Conclusion: Energy provision and intake and protein intake did not meet the RNI for Malaysians among older adults in RSK Cheras, Selangor. However, the adequacy of nutrition provision and plate wastage during the one-lunch time were not associated with the risk of malnutrition.